Analysis of Common Pathways and Markers From Non-Alcoholic Fatty Liver Disease to Immune-Mediated Diseases - Gallego-Durán, Rocío; Montero-Vallejo, Rocío; Maya-Miles, Douglas; Lucena, Ana; Martin, Franz; Ampuero, Javier; Romero-Gómez, Manuel (Frontiers in Immunology, 2021)
Metabolic associated fatty liver disease (MAFLD) is the most prevalent form of liver disease worldwide, accounting for a high liver-related mortality and morbidity with extensive multi-organ involvement. This entity has displaced viral hepatitis as the main cause of severe forms of hepatic diseases, although the onset and transition of MAFLD stages still remains unclear. Nevertheless, innate and adaptive immune responses seem to play an essential role in the establishment and further progression of this disease. The immune system is responsible of safeguard and preserves organs and systems function, and might be altered under different stimuli. Thus, the liver suffers from metabolic and immune changes leading to different injuries and loss of function. It has been stablished that cell-cell crosstalk is a key process in the hepatic homeostasis maintenance. There is mounting evidence suggesting that MAFLD pathogenesis is determined by a complex interaction of environmental, genetic and host factors that leads to a full plethora of outcomes. Therefore, herein we will revisit and discuss the interplay between immune mechanisms and MAFLD, highlighting the potential role of immunological markers in an attempt to clarify its relationship.